Pembuatan Video Profil Sekolah Menengah Atas Negeri 7 Kota Tangerang Selatan Berbasis Audio Visual Sebagai Media Informasi dan Promosi - Martono, Martono; Triyono, Triyono; Septiani, Roesmita Anggis (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2018)
Promotion media is a tool or means to introduce and offer a product or service or image or company or others so that it can be easily known to the wider community. The oldest promotional media is word of mouth. Then the promotion media began to appear in the form of newspapers, radio, magazines, posters, banners and so on. This medium is very effective, but have advantages and disadvantages. Increasingly developing technology is also a media campaign that the more creative, more interesting, and more innovative, including the media campaign in the form of multimedia-based video profiles. High School State 7 Tangsel City one of the government agencies engaged in education has not had the means to promote and inform the development of schools to the public. By using a profile video is expected to be a tool of promotion and information to the community as well as documentation. The purpose of this research is to help the school how to promote and provide school information to large communities but in a more creative way. about high-value targets, This research uses data collection methods, namely observation and interview. Problem approach metology includes problem definition, needs analysis, planning, creating a video profile, video editing, testing.this research is certainly very useful for the school other than that it’s good as a documentary about school. Keywords: Media Promotion, Video Profile, Audio Visual